1986
DOI: 10.1128/aac.30.3.423
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activity and beta-lactamase stability of two oral cephalosporins, ceftetrame (Ro 19-5247) and cefetamet (Ro 15-8074)

Abstract: Ceftetrame and cefetamet (Ro 15-8074), two new orally administered aminothiazolyl imimomethoxy cephalosporins, inhibited hemolytic streptococci and Streptococcus pneumoniae at .0.5 ,ug/ml but were less active against staphylococci than were cephalexin and cefaclor. They did not inhibit S. faecalis, S. faecium, Listeria monocytogenes, Corynebacterium JK species, or Pseudomonas aeruginosa. Haemophilus influenzae, Branhamella catarrhalis, and Neisseria gonorrhoeae, including ampicillin-resistant isolates, were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
17
1
1

Year Published

1988
1988
1992
1992

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 9 publications
3
17
1
1
Order By: Relevance
“…T-2525 (cefterame) is the biologically active product of the orally administered prodrug (T-2588). T-2525 is active against gram-negative bacteria and Streptococculs pneumoniae, but is less active than cefaclor against staphylococci (2,11,13). R-3746 is the biologically active product of CS-807.…”
mentioning
confidence: 99%
“…T-2525 (cefterame) is the biologically active product of the orally administered prodrug (T-2588). T-2525 is active against gram-negative bacteria and Streptococculs pneumoniae, but is less active than cefaclor against staphylococci (2,11,13). R-3746 is the biologically active product of CS-807.…”
mentioning
confidence: 99%
“…In contrast, cefixime did not elevate enzyme levels in this strain and was thus very active against it (MIC, <0.06 ,ug/ml). The variable to strong inducer activities of cefixime and cefuroxime for M. morganii may explain the diminished activities seen by other investigators in tests with a large number of strains of this species (17). Overall, the greater in vitro potency of cefixime over cefuroxime seen in this and other studies could be only partly explained by differences in stability to and/or induction of P-lactamases.…”
Section: Methodsmentioning
confidence: 35%
“…Thus, in this study, only 7 of 50 members of the Enterobacteriaceae were resistant to cefaclor but susceptible to cephalexin. A number of other investigators have also observed this difference in ,-lactamase stability between cefaclor and cephalexin (1,2,8,11,16,17,20,26). However, the difference is most apparent when a cephalosporin rather than a penicillin is used as the standard for comparison.…”
Section: Methodsmentioning
confidence: 83%
See 2 more Smart Citations